Kompleksnaya otsenka mezhsistemnykh otnoshenij funktsionalnykh reaktsii organizma na fizicheskuyu hagruzku - Romanchuk, A. P. (Teorija i Praktika fiziceskoj Kul'tury, 2002)
The studying of features of functional mutual relations in the group of persons engaged in physical culture was the purpose of this paper. The complex research including the survey of 55 examinees engaged in physical culture and 50 persons of control group was carried out. The results of the carried out complex researches had allowed allocating the number of attributes showing the intersystem mutual relation at the persons engaged in physical culture. They cardinally differ from parameters in control group and reflect features of adaptation to physical loads in some cases were revealed.